Solid state NMR: Principles, methods, and applications - Muller, Klaus; Geppi, Marco (Weinheim: Wiley-vch, 2021)
Solid State NMR: Principles, Methods, and Applications offers a systematic introduction to the theory, methodological concepts, and major experimental methods of SSMR spectroscopy. Exploring the unique potential of SSNMR for the structural and dynamic characterization of soft and either amorphous or crystalline solid materials, this comprehensive textbook provides foundational knowledge and recent developments of SSNMR, covering physical and theoretical background, experimental methods, and applications to pharmaceuticals, polymers, inorganic and hybrid materials, liquid crystals, and model membranes. Written by two expert authors to ensure a clear and consistent presentation of the subject
Includes references and index
Solid State NMR: Principles, Methods, and Applications is the ideal textbook for university courses on SSNMR, advanced spectroscopies, and a valuable single-volume reference for spectroscopists, chemists, and researchers in the field of materials.
Keywords: Nuclear magnetic resonance; Solid state physics -- Spectrum analysis -- Materials$1 (BAnalysiss -- Chemistry, Physical and theoretical